UJI EFEKTIVITAS EKSTRAK DAUN BENALU JERUK (Dendrophthoe glabrescens) SEBAGAI NEFROPROTEKTOR TERHADAP KERUSAKAN GINJAL YANG DI INDUKSI DENGAN PARACETAMOL PADA TIKUS PUTIH (Rattus novergicus) - Monika Feronika Ndruru; Edward Kosasih (JBIO: jurnal biosains (the journal of biosciences), 2019)
Abstract Orange parasitic leaves (Dendrophthoe glabrescens) are one of the plants which belong to the family member Loranthaceae that lives on its host plants, namely orange plants as parasites in these plants and are widely used by the community with various properties. This study aimed to determine the effect of the effectiveness of orange parasite leaf extract as a nephroprotector on kidney damage induced by paracetamol in white rats (rattus novergicus). Making extracts was carried out by maceration using 96% ethanol solution. The test animals used were 30 rats (Rattus Novergicus) which were divided into 6 groups. Group I without treatment, group II as negative control, group III as positive control, and group IV, V, and VI who were given orange parasite leaf extract, respectively 100 mg / kg body weight, 200 mg / kg body weight and 400 mg / kg body weight. BB bb for 7 days. On the 8th day all rats except group I, were induced by paracetamol 180 mg / kg BW as the parent of kidney damage. The results showed that the ethanol extract of the leaves of orange parasite with the lowest dose of 100 mg / kg bb was the most effective in nephroprotector activity compared to 200 and 400 mg / kg body weight, and the highest dose of nephroprotector was at a dose of 400 mg / kg can be seen approaching normal renal parenchymal histopathology. Keywords: Kydney, Paracetamol, Orange parasite leaves (Dendrophthoe glabrescens), nephroprotector, and creatinine.